Assessment of Aluminium contaminant in public water supply in Sarawak - Ng, Tze Nyan (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The main objectives of this study are to establish the current levels of aluminum in public drinking water in Sarawak, to determine the sources of aluminum contaminants and to assess water treatment processes that influence the introduction of aluminum in the drinking water. The research method used in this study includes the assessment of the historic water qualities analytical reports available for the last five years (1999-2003) for all drinking water treatment plants in Sarawak relating to aluminum level in particular. Primary data were collected in the field at the selected 7 water treatment plants in order to validate the secondary data. In addition, observations and field investigation were also carried out during the field trip. To obtain additional information, interview survey by using open-ended questionnaires for the staff of the 22 water treatment plants in state were also carried out. The selection of the 7 water treatment plants were done based on the high aluminum violation rates. The sites for the interview survey were done by means of block sampling method whereby 2 water treatment plants were selected from each Division. The mean aluminum level was found to range from 0.53 mg/l to 1.48 mg/l for the past 5 years (1999-2003) in Sarawak, which were 2.65 to 7.4 times higher than the Malaysia Standard and WHO recommended standard of 0.2 mg/l of aluminum level in drinking water. It was also discovered during this study that the high aluminum level was due to the inefficient treatment processes as the aluminum level increased markedly immediately after the addition of Aluminum sulphates in stage 2 of the treatment process. This was proven by ANOVA that there was a significant difference among all the stages of water treatment processes for aluminum (p 0.03). Further Post Hoc Test (LSD) discovered that the raw water (stage I) aluminum level was significantly lower than other stages of treatment processes (a 0.05). It was also discovered through multiple correlations that the level of aluminum is a function of pH, total dissolved solids, turbidity and total suspended solids based on the primary data collected from the field.